2023
DOI: 10.1590/fst.124322
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cactus (Opuntia ficus-indica (L.) Mill) cladodes powder on improving the characteristics and shelf life of low-fat beef and chicken burgers

Abstract: This research aims to investigate the influence of using cactus cladodes powder (CP) as a binder at three concentrations (1%, 3%, and 5%) on selected quality characteristics of low-fat beef and chicken burgers after formulation and during freeze storage (-18 °C) for 100 days, in comparison to control treatments without CP. Using CP at 3% and 5% influenced (p < 0.05) the proximate composition of the formulated burgers, while 1% CP did not influence the proximate composition significantly. Cooking loss was decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…This has a healthy positive effect by decreasing lipid content by 9.22%. According to a recent study by Al-Marazeeq et al (2023), adding cactus cladodes powder to low-fat beef and chicken burgers had a marked effect on the reduction of lipid levels. The researchers found that the use of this ingredient significantly lowered the lipid content in the burgers.…”
Section: Proximate Analysismentioning
confidence: 99%
“…This has a healthy positive effect by decreasing lipid content by 9.22%. According to a recent study by Al-Marazeeq et al (2023), adding cactus cladodes powder to low-fat beef and chicken burgers had a marked effect on the reduction of lipid levels. The researchers found that the use of this ingredient significantly lowered the lipid content in the burgers.…”
Section: Proximate Analysismentioning
confidence: 99%